The earthquake probabilities of Shanxi rift system, China, based on Coulomb stress changes and friction constitutive law - Shi, Fuqiang; Yang, Min; An, Bailin; Hu, Nan; Su, Lina; Yang, Chenyi (Frontiers in Earth Science, 2026)
The Shanxi rift system, a tectonic transfer zone between the Ordos and the North China plain, has experienced multiple strong earthquakes that have caused dev-astating disasters. Based on historical records and paleoseismic investigations, three seismic gaps with high seismic risk are still hanging in the Shanxi rift, posing a signifi-cant threat to the local population and economy. To better assess the seismic hazard potential of the Shanxi rift system, here we modeled the Poisson probability of earthquake occurrence by employing the Coulomb stress changes and friction constitutive law. The result indicated that several faults with high cumulative Poisson probability are predominantly located within two seismic gaps in the Datong and Taiyuan basin and the cumulative Poisson probability for M ≥ 6 earthquake exceeds 0.9 within the next 30 years. Our research provides valuable insights for assessing future seismic hazards in the Shanxi rift system, and may serve as a reference for disaster mitigation strategies and risk reduction efforts.